Electrochemical α-C(sp3)–H/N–H Cross-Coupling of Isochromans and Azoles - Guoping Li; Bing Yan; Liangliang Wu; Yabo Li; Xinqi Hao; Ming Gong; Yangjie Wu (Molecules, 2024)
Isochroman and azole moieties are both present in a wide variety of biologically active molecules. Their efficient combination under mild reaction conditions is beneficial for obtaining small-molecule drug candidates. In this paper, we describe electrochemical α-C(sp3)–H/N–H cross-coupling reactions between isochromans and azoles, yielding products in moderate to excellent yields. This protocol does not require any catalysts or exogenous oxidants and can be performed at room temperature under air. Control experiments and cyclic voltammetry showed that the reaction may proceed through both radical coupling and nucleophilic addition processes.